2020
DOI: 10.15252/embj.2020104469
|View full text |Cite
|
Sign up to set email alerts
|

A unique bacterial tactic to circumvent the cell death crosstalk induced by blockade of caspase‐8

Abstract: Upon invasive bacterial infection of colonic epithelium, host cells induce several types of cell death to eliminate pathogens. For instance, necroptosis is a RIPK‐dependent lytic cell death that serves as a backup system to fully eliminate intracellular pathogens when apoptosis is inhibited; this phenomenon has been termed “cell death crosstalk”. To maintain their replicative niche and multiply within cells, some enteric pathogens prevent epithelial cell death by delivering effectors via the type III secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 54 publications
1
38
0
1
Order By: Relevance
“…Growing evidence has shown an interplay between PCD pathways and microbial factors, suggesting that these pathways may have played important roles during mammalian co-evolution with microbes [142] , [143] . Many pathogens carry microbial effectors that can actively enhance cell viability by blocking PCD pathways or by activating proliferation pathways [144] , [145] . It is likely that host cells have developed complex regulation and interconnection of cell death pathways to overcome the challenges presented by such microbial effectors.…”
Section: Panoptosis In Diseasementioning
confidence: 99%
“…Growing evidence has shown an interplay between PCD pathways and microbial factors, suggesting that these pathways may have played important roles during mammalian co-evolution with microbes [142] , [143] . Many pathogens carry microbial effectors that can actively enhance cell viability by blocking PCD pathways or by activating proliferation pathways [144] , [145] . It is likely that host cells have developed complex regulation and interconnection of cell death pathways to overcome the challenges presented by such microbial effectors.…”
Section: Panoptosis In Diseasementioning
confidence: 99%
“…Characterization of the activity of bacterial effector proteins has revealed new classes of enzymes as well as unique post-translational protein modifications. For example, EspL from EPEC and OspD3 from Shigella are members of a novel family of cysteine protease effectors that can block necroptotic cell death by cleaving and inactivating the RHIM-containing proteins, RIPK1 and RIPK3 [30,31]. NleE from EPEC and OspZ from Shigella are S-adenosyl-Lmethionine (SAM)-dependent methyltransferases that modify a cysteine residue in the zinc finger domains of TAB2 and TAB3, thereby preventing their interaction with ubiquitinated TRAF proteins and leading to inhibition of NF-κB activation [20,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work showed that during early infection of epithelial cells, Shigella uses the T3SS effector OspC3 to prevent caspase‐4‐dependent pyroptotic death (Kobayashi et al , ). Ashida et al () have now demonstrated the T3SS‐dependent inhibition of the interconnected caspase‐8 and necroptotic pathways.…”
Section: Shigella Fights To Maintain Its Replicative Niche Within Epimentioning
confidence: 96%
“…By screening mutant strains of S. flexneri that lack T3SS‐secreted effectors in HT29 human colon epithelial cells, Ashida et al () identified OspD3 as an inhibitor of necroptosis. Further analysis showed that OspD3 is a protease that cleaves within the RHIM domain of essential necroptotic factors RIPK1 and RIPK3, targeting them for degradation.…”
Section: Shigella Fights To Maintain Its Replicative Niche Within Epimentioning
confidence: 99%
See 1 more Smart Citation